2001
DOI: 10.1021/jm010152k
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Model for Estimating Oral Bioavailability of Drugs in Humans and Other Species from Their Caco-2 Permeability and in Vitro Liver Enzyme Metabolic Stability Rates

Abstract: This paper describes a graphical model for simplifying in vitro absorption, metabolism, distribution, and elimination (ADME) data analysis through the estimation of oral bioavailability (%F) of drugs in humans and other species. This model integrates existing in vitro ADME data, such as Caco-2 permeability (P(app)) and metabolic stability (percent remaining - %R) in liver S9 or microsomes, to estimate %F into groups of low, medium, or high regions. To test the predictive accuracy of our model, we examined 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…The pharmacokinetic parameters were calculated using a noncompartmental model in WinNonlin Professional (Version 5.2.1, Pharsight Corp; Mountain View, CA, USA). In vitro metabolic stability of PQ-69 and DPCPX was investigated using rat and human liver microsomes in procedures similar to those previously described [15]. The incubations (5 μM parent drug, 0.5 mg/ml microsomal protein, 0.1 M phosphate buffer) were started by the addition of 1 mM NADPH solution after a 5-min preincubation at 37°C and were terminated after 60 min.…”
Section: Measurement Of Pa2 Valuesmentioning
confidence: 99%
“…The pharmacokinetic parameters were calculated using a noncompartmental model in WinNonlin Professional (Version 5.2.1, Pharsight Corp; Mountain View, CA, USA). In vitro metabolic stability of PQ-69 and DPCPX was investigated using rat and human liver microsomes in procedures similar to those previously described [15]. The incubations (5 μM parent drug, 0.5 mg/ml microsomal protein, 0.1 M phosphate buffer) were started by the addition of 1 mM NADPH solution after a 5-min preincubation at 37°C and were terminated after 60 min.…”
Section: Measurement Of Pa2 Valuesmentioning
confidence: 99%
“…Absorption in vivo is a complex phenomenon, involving several possible mechanisms, although passive diffusion has been identified as the predominant mechanism of gastrointestinal absorption for most commercial drugs. 4 The most relevant factors that regulate the passive diffusion of drugs across the gastrointestinal mucosa are their physicochemical properties, including lipophilicity, solubility, polarity and ionization status. Physiological characteristics such as gastric emptying time and pH conditions throughout the gastrointestinal tract (GIT) also affect oral absorption.…”
Section: General Pk Principlesmentioning
confidence: 99%
“…It is estimated that between 80-95% of commercial drugs are absorbed primarily by passive diffusion 17,18 , and thus an assay to quantify permeability coefficients due to passive diffusion would be of great interest to the pharmaceutical industry. It has previously been demonstrated that giant vesicles are stable in microfluidic flows, and show potential for membrane transport studies 9 .…”
Section: Figure 1a Schematic Of Optical Setup Broadband White Lightmentioning
confidence: 99%